MODEL SISTEM PENUNJANG KEPUTUSAN PENENTUAN JURUSAN BAGI SISWA SMA MENGGUNAKAN METODE TOPSIS (STUDI KASUS YADIKA NATAR) - Sushanti Saleh (IIB Darmajaya, 2016)
Natar Yadika SMA is one of the senior high school in Bandar Lampung which is located on Jl. Sitara No. 84 Muara Putih Natar, South Lampung. SMA Yadika Natar has two courses, namely science and social studies. At each new admissions SMA Yadika Natar has determined the majors for students done by the student in the student section which process refers to the value of report cards, results of written tests, and the interests of students who then recapitulated and calculation. A process which has been running at high school Natar Yadika can cause several problems including, the selection is not objective (results of calculations which are not in accordance with the interests of students), there can be errors in the calculation(HumanError). In order to improve objectivity in determining the majors in high school Yadika Natar. the research build a Decision Support System (DSS) model in the determination of the majors for students / high school Yadika Natar. The system uses a method (TOPSIS) Technique for Order Preference by Similarity to Ideal Solution to the stages of the intelligence phase, the design phase, the selection phase and the implementation phase.Decision support systems in school Yadika Natar which includes determining the majors for students / student is expected to increase the objective assessment and provide the right decisions with the best results in the establishment of a department Keywords— Decision Support System, TOPSIS method, determination of the Department.